Patenting Matters, Not Patents: Firm Market Value in Indian Manufacturing. (February 2018) - Singh, Shailu
This article looks at the association between firm market value and patenting activity in the Indian manufacturing sector, using a matched panel dataset of 380 firms spanning 22 industry groups over the period 2001–2010. To see whether the very act of patenting matters or not we introduce variation through an indicator variable indicating a firm's patenting status, whereas to see whether having a larger number of patents matters for firm value we employ a patent stock variable. Differences in the response of firm market value to variations in these two different ways of capturing patents provide evidence for the signalling role of patents in the context of Indian manufacturing. The empirical investigations indicate that while firms that use patents to protect their innovations have a significantly higher market value than firms that do not, an increase in the number of patents granted to a firm is associated with higher market value only for firms at the lowest end of the market value distribution. The results are consistent with the explanation that patents serve as signals of firm quality.